Enzyme-responsive polymer composites and their applications - Showkat, Ahmad Bhawani; Mehvish, Nisar; Abu, Tariq; Khalid M., Alotaibi; Mohd Razip, Asaruddin (Woodhead Publishing, 2021)
Enzymes play a vital role in a broad spectrum of fundamental physiological processes and therefore could be exploited as biological triggers to achieve a controlled release of cargo at the desired site. Enzyme-responsive materials are a class of stimuli-responsive materials with a variety of applications in biological systems. They have been proved to be potential biomaterials, biomedicine, and biosensing candidates. These types of smart materials undergo macroscopic changes when triggered by a selective action of enzymes. This idea has been applied successfully for the development of drug carrier systems where the tissue of interest is targeted by the release of cargo triggered by the catalytic action of an enzyme. This chapter mainly emphasizes on the few key enzyme-responsive nanomaterials such as proteases, lipases, and glucosidases and oxidoreductases for various biomedical applications.